Strategi Penyelesaian Pembiayaan BermasalahPada Pembiayaan Murābahah(Studi Kasus KJKS BMTKube Colomadu Sejahtera) - Nurrosyidah, Anis Mufarrihah; , Drs. Harun, MH (2016)
The issue studied in this research is the analysis of the troubled financing resolution on the murābaḥah financing in KJKS BMT Kube Colomadu Sejahtera adjusted with Dewan Syariah Nasional Majelis Ulama Indonesia's fatwa number: 47/DSN-MUI/II/2005 about the settlement of murābaḥah's receiveables for customers who can't afford to pay . Thereby, the purpose of this research is to determine the settlement financing strategy of troubled murābaḥah conducted by KJKS BMT Kube Colomadu Sejahtera and adjusted with DSN MUI's fatwa. In order to achieve that goal, researcher has used field research with methods of data collection by ways of interview, documentation and observation. The data source is KJKS BMT Kube Colomadu Sejahtera. As for the data analysis, it was done using descriptive evaluative method. From the research's results, it is obtained that the causes of troubled financing can come from the customer and BMT itself. As for the completion of the financing strategy for the troubled murābaḥah conducted by KJKS BMT Kube Colomadu Sejahtera is prevention and rescue effort for the troubled financing. Prevention efforts, included: a. cash collection, b. rescheduling, c. reconditioning, d .restructuring. Meanwhile, settlement efforts has done by executing settlement collateral/guarantee, either with the disbursement of cash collateral, billing to the guarantor, takeover of the collateral by BMT, collateral sales voluntarily or through auction.